Estimativa dos valores dos atributos físicos de um solo típico da baixada cuiabana para fins de balanço hídrico - Lotufo, Juliana Barbosa da Silva (2018)
The climatological water balance is applied to analyze the water availability in the soil, being useful in the characterization of temporal fluctuations of periods with surplus or deficiency. The predominant soils of Baixada Cuiabana have physical characteristics unfavorable to the storage of water for the plants. In this sense, the objective of this work was to classify the environmental water supply and to identify the physical attributes representative of a typical soil of the Baia Cuiabana for purposes of sequential water balance. The Sequential Water Balance (BHS) was estimated from daily data of climatological variables, from the period from 2009 to 2017, obtained from a micrometeorological tower equipped with sensors to determine the flow densities of evapotranspiration located in a Cerrado area in the Baixada Cuiabana and reference evapotranspiration data from the Padre Ricardo Remetter Climatological Station. The actual evapotranspiration estimated by Bowen's ratio in the Cerrado area was used as a comparative standard, adjusting soil bulk density, effective depth, field capacity and permanent wilt point to estimate the same actual evapotranspiration from that location at from BHS, so that the difference between both estimates of actual evapotranspiration is the lowest possible. According to the evapopluviograma (Ometto, 1981), considering the data series from 2008 to 2017, the study area was classified with a higher percentage in the humid class (32.20%). The highest values of precipitation and evapotranspiration occurred in the same season, spring-summer. The soil physical attributes values were estimated: field capacity (15.73%), permanent wilting point (2.37%), effective depth (906.17 mm), apparent density (1660 kg/m3 ), fraction of available water and available water capacity (200.97 mm). However, analyzing the estimated data it was verified that they do not match the local reality, thus, concluding that it was not true the hypothesis that from the method used in the present study it would be possible to characterize the physical attributes of the soil of the region.